2001
DOI: 10.1111/j.1151-2916.2001.tb01062.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Rheology of Calcium Aluminosilicate (Anorthite) Glass‐Ceramics under Uniaxial and Triaxial Loading

Abstract: The high-temperature creep behavior of two fine-grained (ϳ3 m) anorthite-rich glass-ceramics was characterized at ambient pressure and under a confining pressure of ϳ300 MPa. Experiments were done at differential stresses of 15-200 MPa and temperatures of 1200°-1320°C. Of the two materials, one had a tabular (lathlike) grain structure with finely dispersed second phase of mullite, mostly in the form of ϳ3-5 m grains comparable to that of the primary anorthite phase, whereas the other had an equiaxed grain morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It is conceivable that temperature steps induce a transient period of enhanced dislocation activity. Possibly, the high activation energy may be attributed to cavitation since the formation of new surface requires additional energy as suggested by Nair et al [2001]. These authors deformed tabularshaped anorthite mullite ceramics and found a high creep activation energy and extensive cavitation.…”
Section: Deformation Mechanismmentioning
confidence: 92%
See 2 more Smart Citations
“…It is conceivable that temperature steps induce a transient period of enhanced dislocation activity. Possibly, the high activation energy may be attributed to cavitation since the formation of new surface requires additional energy as suggested by Nair et al [2001]. These authors deformed tabularshaped anorthite mullite ceramics and found a high creep activation energy and extensive cavitation.…”
Section: Deformation Mechanismmentioning
confidence: 92%
“…Nair et al [2001] observed strong cavitation in synthetic anorthite aggregates with ≈10% mullite added when deformed at ambient pressure. Cavitation was suppressed at elevated pressures of 300 MPa.…”
Section: Comparison With Other Studies On Cavitation and Fluid Redistmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11] Furthermore, the application of CAS-based ceramic composites to a high temperature and high pressure environment was largely hindered by the relatively little knowledge of mechanical, microstructural and textural data of CAS and CAS-based composites from laboratory tests. 11,[13][14][15][16] (2) CAS crystal is triclinic with the lowest crystallographic symmetry. The relative activity of different slip systems and dynamic recrystallization in dislocation creeping CAS under varying physical and chemical conditions are still poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present our experimental results on the mechanical properties and microstructures of monolithic calcium aluminosilicate (CAS or anorthite: CaAl 2 Si 3 O 8 ) aggregates, particulate and layered composites with equal volume fractions of quartz (SiO 2 ) and CAS, deformed in axial compression (σ 1 > σ 2 = σ 3 > 0, where σ 1 , σ 2 , σ 3 are the maximum, intermediate and least compressive principal stresses, respectively) at temperatures of 1173-1473 K, been carried out on monolithic CAS and other plagioclase feldspars under uniaxial compression (σ 1 > σ 2 = σ 3 = 0) at ambient pressure, [5][6][7][8][9][10][11] it remains uncertain if the results from small strain creep tests are able to be extrapolated to other conditions because a small amount of strain is usually insufficient for steady-state microstructure to occur. 12 Cavitation often occurs in the samples deformed at ambient pressure.…”
Section: Introductionmentioning
confidence: 99%